Pharmacological and Toxicological Threshold of Bisammonium Tetrakis 4-(N,N-Dimethylamino)pyridinium Decavanadate in a Rat Model of Metabolic Syndrome and Insulin Resistance - Samuel Treviño; Alfonso Díaz; Eduardo Sánchez-Lara; Víctor Enrique Sarmiento-Ortega; José Ángel Flores-Hernández; Eduardo Brambila; Francisco J. Meléndez; Enrique González-Vergara (Bioinorganic Chemistry and Applications)
Vanadium(IV/V) compounds have been studied as possible metallopharmaceutical drugs against diabetes mellitus. However, mechanisms of action and toxicological threshold have been tackled poorly so far. In this paper, our purposes were to evaluate the metabolic activity on dyslipidemia and dysglycemia, insulin signaling in liver and adipose tissue, and toxicology of the title compound. To do so, the previously reported bisammonium tetrakis 4-(N,N-dimethylamino)pyridinium decavanadate, the formula of which is [DMAPH]4(NH4)2[V10O28]·8H2O (where DMAPH is 4-dimethylaminopyridinium ion), was synthesized, and its dose-response curve on hyperglycemic rats was evaluated. A Long–Evans rat model showing dyslipidemia and dysglycemia with parameters that reproduce metabolic syndrome and severe insulin resistance was generated. Two different dosages, 5 µmol and 10 µmol twice a week of the title compound (equivalent to 2.43 mg·V/kg/day and 4.86 mg·V/kg/day, resp.), were administered intraperitoneal (i.p.) for two months. Then, an improvement on each of the following parameters was observed at a 5 µmol dose: weight reduction, abdominal perimeter, fatty index, body mass index, oral glucose tolerance test, lipid profile, and adipokine and insulin resistance indexes. Nevertheless, when the toxicological profile was evaluated at a 10 µmol dose, it did not show complete improvement, tested by the liver and adipose histology, as well as by insulin receptor phosphorylation and GLUT-4 expression. In conclusion, the title compound administration produces regulation on lipids and carbohydrates, regardless of dose, but the pharmacological and toxicological threshold for cell regulation are suggested to be up to 5 µmol (2.43 mg·V/kg/day) dose twice per week.